Food and fluid intake during exercise - Maughan, R. J. (Canadian Journal of Applied Physiology, 2001)
The intake of fluid and CHO offers benefits to the performance of a number of sports events and exercise activities. The effects of dehydration on performance are now well known, with the penalties ranging from subtle, but often important, decrements in performance at low levels of fluid deficit to the severe health risks associated with substantial fluid losses during exercise in the heat. Although evidence of the beneficial effects of CHO intake during exercise have existed for over 70 years, sports scientists are still to discover all the situations in which benefits occur and to explain the mechanisms involved. Optimal strategies for CHO and fluid intake during exercise are yet to be fine-tuned, and ultimately will be determined by practical issues such as the opportunity to eat or drink during an event, and gastrointestinal comfort.